Analisis Persepsi Penonton Tentang Fenomena Mistis Dalam Film Badarawuhi di Desa Penari - Nai, Maria Chandrayani Bai; Zahra, Putri Patimatul; Saharani, Shakila Mahsa (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
In this research, the researcher investigates how the audience understands and interprets aspects of mystical phenomena contained in the movie "Badarawuhi di Desa Penari". These mystical phenomena can include various elements, such as local beliefs, myths, or spiritual practices presented in the context of the story. The research will focus on how the representations of local traditions and social norms presented in the movie influence the audience's perception of the culture. In knowing the perception, the researcher uses Alex Sobur's cognitive theory to explore the meaning that exists in the audience. The research method used is a qualitative descriptive method that allows a more detailed explanation of the principles found. The data was collected through in-depth interviews in person and online via WhatsApp with the informants. This research reveals that continuous exposure to horror films can influence viewers' perception and increase their susceptibility to believing in the supernatural elements portrayed in these movies. However, it is crucial to acknowledge that individual beliefs vary and should be respected. Horror films can serve as a window into the cultural beliefs and practices surrounding supernatural phenomena in different societies. Therefore, it is paramount to always respect and value the local beliefs of the community, regardless of one's location.